Analisis Kesiapan Pengusaha Kendang Dalam Memasuki Era New Normal - Melati Atika Sari; Farida Rahmawati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
The Covid-19 pandemic has resulted innegative impact on the business world that triggers a decrease in purchasing power, a decrease in production, a decrease in demand, and a decrease in turnover. To restore economic activity, the government made a new normal policy strategy as an adaptation to new habits. The purpose of this study was to analyze the effect of age, length of business, labor, and turnover on readiness in the new normal era at the drum industry center. The research method used in this research is quantitative method. The number of samples used were 50 respondents consisting of drumentrepreneurs. The analytical method used is binary logistic regression analysis. The results showed thatage hascoefficient value 0.8591748 and p value 0.043 (less than alpha 0.05) it shows that age has a positive and significant influence on the readiness of drum entrepreneurs in the new normal era.. The length of business has a coefficient value of 1.421117 and a p value of 0.001 so that it has a positive and significant impact on the readiness of drum entrepreneurs. Labor has a positive and significant effect onreadiness of drum entrepreneurs with coefficient value0.6885818 and a p value of 0.026.Turnover has a coefficient value of 1 and a p value of 0.277, thus turnover has a positive and insignificant effect because the p value is greater than alpha